Dimensi Budaya dalam Peningkatan Sumber Daya Manusia Melalui Implementasi Total Quality - - Rosidah (Universitas Negeri Yogyakarta, 2004)
Human resource is key factor of organization development for public and business organization. Organization development orientation does not concern directly with human being. However, its implication is refer to human resource. Therefore, its existence is needed to be given a serious attention. One of methods is Total Quality approach. This paper discusses some problems of developing a good quality of working culture.